Employee Ownership and Attitudes Toward the Union: An Empirical Study - Long, Richard J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
This article explores the relationship between employee ownership and attitudes toward the union by reporting the results of an empricial study of a unionized Canadian trucking company recently purchased from it s former corporate owner by most of its workers and managers. Results indicated that most workers— both union and non-union— did not believe that unionization was either incompatible with employee ownership or unnecessary.